Erbil, Irak: Survey im Stadtgebiet von Erbil - Hausleiter, Arnulf; van Ess, Margarete (e-Forschungsberichte des DAI, 2023)
A first season of surface survey in the city of Erbil identified altogether 178 survey squares within the 60 m-Ring Road. Archaeological sampling concentrated on the area within the 30 m-Road providing predominantly ceramics from the Middle Islamic period. Iron Age pottery is clearly less represented, and material from preceding periods has not yet been recorded. A number of topographical features was identified, some of them probably ancient settlement mounds. The Pleiades satellite image, which serves as cartographic foundation for the project, has been rectified by geodetic methods aimed at developing a Digital Terrain Model.